PENGARUH CELEBRITY WORSHIP DAN LITERASI KEUANGAN TERHADAP COMPULSIVE BUYING PENGGEMAR K-POP DALAM MEMBELI MERCHANDISE - Ningsi, Ningsi; Aisyah, Siti; Nur Abdi, Muhammad (Ekonomi & Bisnis, 2025)
This study aims to analyze the influence of celebrity worship and financial literacy on compulsive buying among K-Pop fans when purchasing merchandise. The research employs a quantitative approach, collecting data through questionnaires from 98 respondents who purchase merchandise online. Data analysis was conducted using multiple linear regression through SPSS version 27. The results indicate that celebrity worship has a positive and significant effect on compulsive buying, with a regression coefficient of 0.350 and a significance value of 0.003 < 0.05. Additionally, financial literacy also has a positive and significant effect on compulsive buying, with a regression coefficient of 0.375 and a significance value of 0.000 < 0.05. These findings suggest that the higher an individual's level of celebrity worship and financial literacy, the greater their tendency to engage in compulsive buying. Keywords: Celebrity worship, financial literacy, compulsive buying.